Colour change of greenlip abalone, Haliotis Laevigata Donovan, fed dried macroalgae meals in concurrent laboratory and on‐farm trials - Mark Purvis; Krishna‐Lee Currie; Amy L. Bates; Matthew S. Bansemer; Jian G. Qin; James O. Harris; David A. J. Stone (New Zealand Journal of Marine and Freshwater Research, 2025)
In Australia, cultured greenlip abalone ( Haliotis laevigata ) are fed formulated diets that lack macroalgae. This has resulted in a pale lip colour in contrast to the vivid green lip colour of wild abalone. We evaluated the effects of supplementing 15% dried macroalgae meal, using either commercially available macroalgae meal (MSM) or harvested Gracilaria cliftonii, on colour change in greenlip abalone . Abalone were fed the respective diets in a three month laboratory trial and an additional four month on‐farm trial. The inclusion of MSM into formulated abalone diet did not change lip, foot, or shell colour, whereas the G. cliftonii meal treatment changed lip and shell colour. The laboratory study was extended for another three months. Greenlip abalone either: (1) continued to be fed their experimental diet; or (2) the abalone were fed a diet with no dried algal meal. The colour changes observed in the first study were retained for one month, after which the colour declined. The addition of 15% G. cliftonii meal to formulated diets can be used to manipulate greenlip abalone lip and shell colour. A minimum of three months is recommended and abalone should be harvested within one month to maintain the desirable colour changes.